2016
DOI: 10.1038/srep21752
|View full text |Cite
|
Sign up to set email alerts
|

SGLT1 activity in lung alveolar cells of diabetic rats modulates airway surface liquid glucose concentration and bacterial proliferation

Abstract: High glucose concentration in the airway surface liquid (ASL) is an important feature of diabetes that predisposes to respiratory infections. We investigated the role of alveolar epithelial SGLT1 activity on ASL glucose concentration and bacterial proliferation. Non-diabetic and diabetic rats were intranasally treated with saline, isoproterenol (to increase SGLT1 activity) or phlorizin (to decrease SGLT1 activity); 2 hours later, glucose concentration and bacterial proliferation (methicillin-resistant Sthaphyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 41 publications
2
45
1
1
Order By: Relevance
“…Several studies have utilized diabetic mouse models to demonstrate the impact that excess glucose has on increasing bacterial proliferation within the lungs (35,36). Levels of glucose in the lungs are maintained lower in order to prevent colonization of pathogens (37).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have utilized diabetic mouse models to demonstrate the impact that excess glucose has on increasing bacterial proliferation within the lungs (35,36). Levels of glucose in the lungs are maintained lower in order to prevent colonization of pathogens (37).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, genetic impairment of sugar transport pathways in P. aeruginosa and S. aureus that limited sugar uptake had a similar effect on bacterial growth/survival in the lung to that of dapagliflozin (Pezzulo et al, ; Garnett et al, ; Gill et al, ). Reduction of airway glucose in the distal mouse lung by manipulation of glucose transport pathways also reduced bacterial load (Oliveira et al, ). Furthermore, we previously showed that treatment with the biguanide metformin reduced lung epithelial permeability and glucose flux into the lung lumen without affecting blood glucose concentration and inhibited the growth/survival of S. aureus and P. aeruginosa in diabetic mice (Garnett et al, ; Patkee et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The SGLT1 isoform is expressed in alveolar epithelium, where it contributes to sodium, glucose and fluid absorption (Bodega et al, ). Phlorizin, an inhibitor of SGLT1/2, reduced lung liquid and glucose absorption, increasing luminal glucose concentrations with potential adverse effects of pulmonary oedema and increased bacterial proliferation (Oliveira et al, ). Dapagliflozin, which has ~200‐fold selectivity for SGLT2 over SGLT1 (Han et al, ) had no effect on lung fluid or glucose absorption, providing further evidence for pulmonary safety of this drug and no function of SGLT2 in the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IR spectral modes of biological samples, such as saliva, may be considered as biochemical fingerprints that correlate directly with the presence or absence of diseases, and, furthermore, provide the basis for the quantitative determination of several analytes for monitoring several diseases and to diagnostic interest [21,22]. The potential of salivary diagnostic for diabetes by IR spectroscopy using barium fluoride (BaF 2 ) slides was suggested previously [23], however, the efficacy of DM monitoring in insulin-treated conditions using ultra-low volumes of saliva remains unknown.…”
Section: Introductionmentioning
confidence: 99%